Addressing Spillovers from Prolonged U.S. Monetary Policy Easing - Cecchetti, Stephen (IMF Working Papers; Working Paper ;, 2021)
There is growing recognition that prolonged monetary policy easing of major economies can have extraterritorial spillovers, driving up financial system leverage in other countries. When faced with such a rise of threats to financial stability, what can countries do? Specifically, is there a role for macroprudential tools, capital controls or foreign exchange intervention in safeguarding financial stability from risks arising externally? We examine the efficacy of these policy interventions by exploring whether preemptive or reactive policy interventions can mitigate such risks. Using a sample of 950 bank and nonbank financial firms across 28 non-U.S. economies over the past two decades, we show that if policymakers are able to implement policies prior to an additional consecutive decline in U.S. interest rates, financial institutions do not increase their leverage by as much as they otherwise would. By contrast, it is more difficult to counter the spillovers with reactive policy interventions. In practice, however, policymakers need to remain cautious about the timing of preventative tightening, especially when their economies face large negative shocks such as a pandemic.